1995
DOI: 10.1002/ajmg.1320550416
|View full text |Cite
|
Sign up to set email alerts
|

Fetal akinesia and multiple perinatal fractures

Abstract: Two newborn infants with fetal akinesia sequence were noted to have multiple perinatal fractures of the long bones. The radiographic manifestations are characterized by gracile ribs, thin long bones, and multiple diaphyseal fractures. Consistent histopathologic changes of bone are irregular with focal areas of extreme diaphyseal thinning, thin and long marrow spicules, and with or without callous formation at fracture sites. Pathogenic mechanisms of bone fractures in fetal akinesia sequence and the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Chen et al [15] suggested that Pena-Shokeir syndrome type I is a primary motor neuropathy with diffuse muscle atrophy secondarily emerging from paucity of the anterior horn cells in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [15] suggested that Pena-Shokeir syndrome type I is a primary motor neuropathy with diffuse muscle atrophy secondarily emerging from paucity of the anterior horn cells in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the most often reported histologic abnormalities associated with thin long bones are thin cortices and fractures of the growth plate and diaphysis fractures [Bonaventure et al, 1989;Chen et al, 1995;Kozlowski and Kan, 1988;Rodríguez et al, 1988a,b]. In addition, lesions of the growth plate have not been observed in histologic studies of bones of patients who had diseases characterized by osseous fragility, such as osteogenesis imperfecta [Rodríguez et al, 1988b].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be asymptomatic and found only at autopsy. Chen et al (1995) discuss that these infants with ischemic changes are prone to perinatal fractures. Agapitos et al (1988) reported a case with gastroschisis and agenesis of the leg (both thought to be due to vascular accidents) with CNS hemorrhage.…”
Section: Familial Intrauterine Anoxia And/or Ischemiamentioning
confidence: 97%
“…Scrambled fingers distal overlap Houston, 1981 (case 4-pre axial) Bisceglia et al, 1987Chen et al, 1983 (case 3) Punnett, 1974 (case 1-pre axial) Choi et al, 1986Toriello et al, 1985 (case 2 -post axial) Lazjuk et al, 1978 Pena andShokeir, 1974 Adducted Thumbs RU Synostosis Bisceglia et al, 1987Chen et al, 1983 (case 4-unilateral) Lazjuk et al, 1978 (case 4) Williams et al, 1980 Dislocated Radial Head Syndactyly Chen et al, 1983 (family 2) Lindhout et al, 1985 (case 7) Crane et al, 1981Dislocations Chen et al, 1983 Bisceglia et al, 1987Chen et al, 1983Charollais et al, 2001Chen et al, 1995Chen et al, 1995Herva et al, 1985Herva et al, 1988 Ho, 2000 (family b) Ohlsson et al, 1988Itoh et al, 1991 Erdl et al, 1989Moerman et al, 1983 (case 1 and case 2) Lindhout et al, 1985Punnett et al, 1974 (pyramidal lobe) Toriello et al, 1985Reiser et al, 1990 Erdl et al, 1989Dimmick et al, 1977Lammer et al, 1989Erdl et al, 1985Herva et al, 1985 Dilated Ventricles Moerman et al, 1983 (cases 1, 2) Lazjuk et al, 1978 (case 3) Williams et al, 1980Hydrocephaly Lindhout et al, 1985 reviewed the article, added two case reports (with many additional anomalies) and also published in 1974. Pena and Shokeir added a second incestuou...…”
Section: Polydactylymentioning
confidence: 99%
See 1 more Smart Citation